Oliver October - McCutcheon, George Barr, 1866-1928 (Salt Lake City, UT : Project Gutenberg, 2022)
"Oliver October" by George Barr McCutcheon is a novel written in the early 20th century. The story begins with the birth of Oliver Baxter, junior, on a blizzardy October day in a small town named Rumley, where civic pride and intrigue encapsulate community life. The novel explores the dynamics of small-town relationships, societal expectations, and the quirky events that accompany the arrival of newcomers, particularly focusing on Oliver and his family as they navigate through various hardships and joys of life. The opening of the book sets the stage with the chaotic day of Oliver's birth, overshadowed by a terrible storm and the presence of a band of gypsies that intrigue and frighten the townsfolk. Oliver's father, a timid and nervous hardware store owner, juggles his anxiety about his wife's health during childbirth and the impending sense of urgency brought on by the gypsy camp nearby. The narrative depicts the tumultuous arrival and subsequent reactions by the townspeople as they grapple with the significance of both the birth and the chaotic external circumstances. There is rich characterization from the outset, as the community's curiosity and gossip intertwine with the personal stakes of the Baxter family, establishing a humorous yet poignant backdrop for Oliver$1 (Bs early life and the subsequent challenges he will face as he grows up in this peculiar small town. (This is an automatically generated summary.)s
Release date is 2022-12-14
Al Haines, John Routh & the online Distributed Proofreaders Canada team at https://www.pgdpcanada.net
Keywords: American fiction -- 20th century; Prophecies -- Fiction